Dampak Potensi Kekerasan Dalam Rumah Tangga Terhadap Meningkatnya Angka Perceraian (Studi Kasus di Mahkamah Syar’iyah Meulaboh) - Hanapi, Agustin; Juismaidar, Evi (USRAH: Jurnal Hukum Keluarga Islam, 2024)
Domestic violence (KDRT) has been understood by the community as only the same physical violence, but can also include sexual, psychological, or family neglect. Domestic violence has social implications for divorce in society, because domestic violence can be the cause of divorce. This paper aims to review the legal aspects of domestic violence from the perspective of Islamic Law and Positive Law in Indonesia on the high divorce rate. This article uses a qualitative research method with a case approach. Data was obtained through interviews with related parties. The location of this study was carried out in Aceh using interpretation analysis. Based on research, it was found that domestic violence is motivated by a person's low mental health, low religious values in the family, low education, lack of support from the family, and low values of aqidah and morals, so that from these factors the potential of a person to file for divorce is very high.   Keywords:  Impact, Domestic Violence, and Divorce.